2016
DOI: 10.1097/bor.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the interleukin-23/17 axis in axial spondyloarthritis

Abstract: Purpose of review To highlight and emphasize how new knowledge of mechanisms linked to the IL-23/IL-17 pathway are relevant to the pathophysiology of axial spondyloarthritis (axSpA) and to demonstrate how molecules in IL-23/IL-17 pathway provide novel therapeutic targets for axSpA patients. Recent findings Similar to AS, the increased frequency of Th17 cells in nr-axSpA patients underscores the concept that these disorders can be viewed on a spectrum. Recent findings suggest that the contribution of IL-23/IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 68 publications
(73 reference statements)
0
32
0
1
Order By: Relevance
“…Anti-TNFa and anti-IL-17A agents are currently the only approved classes of biologic therapy for the treatment of patients with AS, and they are widely used for patients in whom the disease is not controlled with conventional treatment (NSAIDs). 7,8,[18][19][20][21][22][23] In this pooled subanalysis of Asian patients from two pivotal phase 3 trials, secukinumab provided rapid and sustained improvements in the signs and symptoms of AS, with ASAS20 and ASAS40 responses achieved in 69.6% and 43.5% of Asian patients compared with placebo (26.1% and 17.4%, respectively) at Week 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-TNFa and anti-IL-17A agents are currently the only approved classes of biologic therapy for the treatment of patients with AS, and they are widely used for patients in whom the disease is not controlled with conventional treatment (NSAIDs). 7,8,[18][19][20][21][22][23] In this pooled subanalysis of Asian patients from two pivotal phase 3 trials, secukinumab provided rapid and sustained improvements in the signs and symptoms of AS, with ASAS20 and ASAS40 responses achieved in 69.6% and 43.5% of Asian patients compared with placebo (26.1% and 17.4%, respectively) at Week 16.…”
Section: Discussionmentioning
confidence: 99%
“…5 Currently, anti-tumor necrosis factor alpha (anti-TNFa) and anti-interleukin-17A (IL-17A) agents are the only class of biologics approved for the treatment of AS, both in Asia and worldwide. 4,[6][7][8] Up to 40% of AS patients experience an inadequate response or intolerance (IR) to anti-TNFa therapies, 4,9,10 and cases of relapse of disease have been reported specifically in Asian patients after completion of short-term treatment with anti-TNFa therapies. 4 Thus, there is an unmet medical need for additional effective treatments for AS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the pathogenesis has centered on description of the Th1 pathway and TNF-alpha (16). Knowledge regarding the mechanisms of the IL17–IL23 pathway has increased with genetic, experimental models and functional data suggesting that it plays a crucial role in SpA (16, 17).…”
Section: Pathophysiology Of Spa and Il17–il23 Axismentioning
confidence: 99%
“…Knowledge regarding the mechanisms of the IL17–IL23 pathway has increased with genetic, experimental models and functional data suggesting that it plays a crucial role in SpA (16, 17). First evidence came from genetic studies that showed protective polymorphisms in the IL-23 receptor gene (rs11209026, Arg381Gln) for AS (18) by impairing function of Th17 cells to produce IL-17 through the IL-23-dependent pathway.…”
Section: Pathophysiology Of Spa and Il17–il23 Axismentioning
confidence: 99%